Nuevos ensayos sobre el entendimiento humano - Leibniz, Gottfried Wilhelm, Freiherr von, 1646-1716; Goberna Falque, Juan R. (Juan Ramón), 1968-; Molina Martínez, Rubén; Leibniz, Gottfried Wilhelm, Freiherr von, 1646-1716. (Tres Cantos, Madrid : Akal, 2017)
Leibniz argues chapter by chapter with John Locke's Essay Concerning Human Understanding, challenging his views about knowledge, personal identity, God, morality, mind and matter, nature versus nurture, logic and language, and a host of other topics.
Online resource; title from ePub title page (Digitalia, viewed September 2, 2019)
Keywords: Locke, John, -- 1632-1704.; Knowledge, Theory of -- Early works to 1800.; Electronic books